Antigen-selective modulation of AAV immunogenicity with tolerogenic rapamycin nanoparticles enables successful vector re-administration. Issue 1 (December 2018) - Meliani, Amine; Boisgerault, Florence; Hardet, Romain; Marmier, Solenne; Collaud, Fanny; Ronzitti, Giuseppe; Leborgne, Christian; Costa Verdera, Helena; Simon Sola, Marcelo; Charles, Severine; Vignaud, Alban; van Wittenberghe, Laetitia; et al.
Abstract Gene therapy mediated by recombinant adeno-associated virus (AAV) vectors is a promising treatment for systemic monogenic diseases. However, vector immunogenicity represents a major limitation to gene transfer with AAV vectors, particularly for vector re-administration. Here, we demonstrate that synthetic vaccine particles encapsulating rapamycin (SVP[Rapa]), co-administered with AAV vectors, prevents the induction of anti-capsid humoral and cell-mediated responses. This allows successful vector re-administration in mice and nonhuman primates. SVP[Rapa] dosed with AAV vectors reduces B and T cell activation in an antigen-selective manner, inhibits CD8+ T cell infiltration in the liver, and efficiently blocks memory T cell responses. SVP[Rapa] immunomodulatory effects can be transferred from treated to naive mice by adoptive transfer of splenocytes, and is inhibited by depletion of CD25+ T cells, suggesting a role for regulatory T cells. Co-administration of SVP[Rapa] with AAV vector represents a powerful strategy to modulate vector immunogenicity and enable effective vector re-administration. Immunogenicity of AAV vectors renders repeated AAV dosing ineffective. Here the authors show that coadministration of nanoparticle-encapsulated rapamycin overcomes AAV immunogenicity through Treg induction, enabling efficient AAV redosing in mice and nonhuman primates.